Ethnobotanical characterization of medicinal plants used in Kisantu and Mbanza-Ngungu territories, Kongo-Central Province in DR Congo - Kibungu Kembelo Pathy; Nzuki Bakwaye Flavien; Belesi Katula Honoré; Wouter Vanhove; Van Damme Patrick (BMC, 2021)
Abstract Background The phytotherapeutic knowledge of the Kongo people in the territories of Kisantu and Mbanza-Ngungu in Kongo-Central Province (DR Congo) is rapidly eroding. To document the remaining knowledge, we conducted an ethnobotanical survey on the most important medicinal plant species and diseases treated with them, as well as plants with therapeutic potential. We also checked for the cultural similarity in medicinal plant knowledge between the two territories and how knowledge about Kongo medicinal plants differs between different social groups. Methods From June 2017 until February 2018 and from February 2019 until April 2019, we conducted a survey with 188 phytotherapists, selected using the snowball method and surveyed using semi-structured interviews. Voucher specimens were taken for identification. Ethnobotanical data were analyzed using medicinal use value (UVs), informant agreement ratio (IARs), informant consensus factor (ICF), and species therapeutic potential (STP). Rahman's similarity index was used for ethno-cultural comparison of medicinal plant knowledge between the two communities. Medicinal knowledge between different social groups was analyzed using non-parametric tests and Poisson regression. Results A total of 231 plants (i.e., 227 botanical species, representing 192 genera and 79 families) were reportedly used to treat 103 diseases. Most abundant taxa were reported for the Fabaceae family (including 11.9% of species and 10.9% of genera). Most reported species (45.0%) were from anthropized areas. Leaves (39.4%), herbs (37.1%), decoction (41.7%), and oral ingestion (72%) were the most frequently cited plant part, botanical form, preparation, and administration method, respectively. Four of all inventoried species showed high UVS (> 0.05), whereas eight had an IAR of one. According to ICF, 31 diseases were mentioned. Highest ICF (≥ 0.4) was observed for hemorrhoids (0.44), amoebiasis (0.43), and itchy rash (0.42). Fifty-four plant species were identified as likely possessing an interesting therapeutic potential. Low ethno-cultural similarity in medicinal knowledge (RSI = 16.6%) was found between the two territories. Analysis of the Kongo medicinal plant knowledge showed that the mean number of reported species and diseases vary considerably depending on gender, type, and residence of therapists (P < 0.05). Conclusion Results prove that the Kongo phytopharmacopeia makes use of interesting medicinal plant species that could be further studied for conservation and pharmacological applications.